Comparative analysis of foam-only versus carbon-plated advanced footwear technology spikes in distance runners - Wu, Y.; Zhang, H.; Wang, S.; Lu, C.; Xing, Q.; Tian, Y.; He, D.; Sun, L.; Shen, Y. (Frontiers in Physiology, 2025)
Background: Advanced footwear technology (AFT) spikes are commonly offered in two configurations: foam only and foam combined with a carbon fiber plate. Whether the plate provides additional metabolic or performance benefits over foam-only designs remains uncertain. Therefore, this study compared physiological, biomechanical, and perceptual responses to two commercially available AFT spikes (Nike ZoomX Dragonfly, foam only; Nike Air Zoom Victory, foam plus carbon plate) in trained and national-level distance runners.